Temperature and Humidity Monitoring Tool Using the Blynk Application for Room Comfort - Mahatmadi Ariq Mayangkara (PUSAT SAINS INDONESIA, 2024)
This research aims to develop a tool that can monitor temperature and humidity which is integrated with the Blynk application, which can be accessed via smartphone. This tool uses a DHT22 sensor to measure temperature and humidity, as well as an ESP32 microcontroller to process data. All components can work well after testing, where the ESP32 can connect and control sensors and display data on the 20x4 LCD. Internet of Things technology is the reference for this system to provide accurate and real-time monitoring, so that it can help users maintain environmental health, especially in closed spaces. Keywords: temperature, humidity, monitoring, Blynk, IoT.